Hailey-Hailey disease responding to thalidomide - K Bala Nanda; Celia Soni Saldanha; Martis Jacintha; Ganesh Kamath (Wolters Kluwer Medknow Publications, 2014)
Familial benign chronic pemphigus or Hailey-Hailey disease (HHD) is a rare autosomal dominant disorder characterized by the development of recurrent blisters and erosions in the intertriginous areas. Various topical and systemic treatment options include corticosteroids, topical 5-fluorouracil, topical vitamin D analogs, topical zinc oxide, dapsone, psoralen plus ultraviolet A, systemic retinoids, cyclosporine, methotrexate, and photodynamic therapy. In recalcitrant cases, further options including, invasive methods such as grenz ray therapy, carbon dioxide laser abrasion, and erbium: YAG laser ablation, dermabrasion, electron beam therapy, botulinum toxin, and full-thickness excision of affected skin with repair by split-thickness grafting have been reported as useful in treatment of HHD. We describe a case of HHD who was treated with several treatment modalities including antibiotics, corticosteroids, and dapsone earlier and when presented to us had a severe recalcitrant disease. Thalidomide, as a modality of treatment has been successfully used in few cases earlier. Our patient responded well to thalidomide.